Rs12329760 Polymorphism in Transmembrane Serine Protease 2 Gene and Risk of Coronavirus Disease 2019 Mortality. (22nd November 2022) - Beheshti Shirazi, Saeedeh Sadat; Sakhaee, Fatemeh; Sotoodehnejadnematalahi, Fattah; Zamani, Mohammad Saber; Ahmadi, Iraj; Anvari, Enayat; Fateh, Abolfazl
Abstract : The protease produced by the transmembrane serine protease 2 ( TMPRSS2 ) gene enhances viral infections and has been linked to severe acute respiratory syndrome coronavirus 2 pathogenesis. Therefore, this study evaluated the association between TMPRSS2 and coronavirus disease 2019 (COVID-19) mortality. TMPRSS2 rs12329760 polymorphism was genotyped using the tetraprimer amplification refractory mutation system-polymerase chain reaction method in 592 dead and 693 improved patients. In the current study, the frequency of TMPRSS2 rs12329760 CC than TT genotypes was significantly lower in improved patients than in dead patients. According to the findings of the multivariate logistic regression test, higher levels of mean age, creatinine, erythrocyte sedimentation rate, C-reactive protein, aspartate aminotransferase, lower levels of 25-hydroxyvitamin D, uric acid, and real-time PCR Ct values and TMPRSS2 rs12329760 CC genotype were observed to be associated with increased COVID-19 mortality rates. In conclusion, the TMPRSS2 rs12329760 CC genotype was a polymorphism linked to a significantly higher incidence of severe COVID-19. Further studies are required to corroborate the obtained findings.